2009
DOI: 10.1002/humu.21021
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperoxaluria type 1: update and additional mutation analysis of theAGXTgene

Abstract: Primary hyperoxaluria type 1 (PH1) is an autosomal recessive, inherited disorder of glyoxylate metabolism arising from a deficiency of the alanine: glyoxylate aminotransferase (AGT) enzyme, encoded by the AGXT gene. The disease is manifested by excessive endogenous oxalate production, which leads to impaired renal function and associated morbidity. At least 146 mutations have now been described, 50 of which are newly reported here. The mutations, which occur along the length of the AGXT gene, are predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 67 publications
6
129
3
2
Order By: Relevance
“…In contrast, G161R destabilized both alleles. In agreement with these results, the G161R mutation has been described in a patient on the major allele, while C253R has been found to cause disease only in combination with the minor allele (Williams et al 2009). We next used IDESA to examine a larger set of diseaserelated variants.…”
Section: Characterization Of Uncharacterized Disease Alleles Of Agtsupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, G161R destabilized both alleles. In agreement with these results, the G161R mutation has been described in a patient on the major allele, while C253R has been found to cause disease only in combination with the minor allele (Williams et al 2009). We next used IDESA to examine a larger set of diseaserelated variants.…”
Section: Characterization Of Uncharacterized Disease Alleles Of Agtsupporting
confidence: 73%
“…For proteins with unknown or undefined functions, identification of disease variants that affect activity but not stability can provide clues to their mechanisms of action. We chose 35 disease variants of AGT from PH1 patients (Williams et al 2009) that showed loss of function (,10% of wild-type AGT activity) in a yeast activity assay based on complementation (Hopper et al 2008). Within this set, we identified 12 mutants that showed good stability in IDESA ( Figure 4B, top), but poor activity in the complementation assay ( Figure 4B, bottom).…”
Section: Characterization Of Uncharacterized Disease Alleles Of Agtmentioning
confidence: 99%
“…A definite diagnosis of PHI had previously been made in another family member (patient 18) by liver biopsy (AGT activity 4.4 mmol/h/mg protein, reference range 19.1-47.9) and had been reconfirmed by molecular testing revealing homozygosity for the AGXT p.D201E mutation. 20 Complete AGXT/GRHPR sequencing and MLPA performed in patients 14 and 15, however, identified the familial p.D201E mutation only in heterozygous state, segregating from the mother. Both girls were initially misclassified as having PHI, based on their severe phenotype in conjunction with results obtained on a liver biopsy from the older girl showing reduced liver AGT activity (15.8 mmol/h/mg protein; a level also compatible with carrier status in an asymptomatic proband).…”
Section: Hoga1 Analysismentioning
confidence: 97%
“…5,[16][17][18] A total of 178 AGXT mutations have been described; the three most common, p.G170R, c.33dupC, and p.I244T, account for approximately 30%, 11%, and 6% of AGXTmutant alleles, respectively; p.I244T is common in Spanish/North African populations. [19][20][21][22][23][24] AGXT p.G170R is associated with mistargeting of the AGT homodimer to mitochondria and the associated unmasking of the p.P11L mitochondrial targeting sequence (MTS) of the "minor" p.P11L/p.I340M haplotype. [25][26][27][28][29] Patients with p.G170R have milder renal disease and respond to pyridoxine treatment, a cofactor that reduces enzyme mistargeting.…”
mentioning
confidence: 99%